FARMERS RELUCTANCE TO USING PROTECTED CULTIVATION IN BAGHDAD PROVINCE AND WAYS TO ADDRESS IT - A. H. Ali; S. O. Fayyadh (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
The study aimed to identify the reasons behind farmers’ reluctance to using protected cultivation in Baghdad province / Al-Karkh and ways to address them. The study community included vegetable farmers who stopped using protected cultivation, distributed among the agricultural divisions affiliated with the Baghdad / Al-Karkh Agriculture Department during 2023. A stratified random sample belonging was chosen namely112farmers. To achieve the study objectives, a questionnaire was prepared consisting of 21 items divided into two areas of reasons and 12 suggestions of treatments. To measure these reasons and treatments, a four-level scale was developed, consisting of four levels according to the importance (strongly agree, agree, somewhat agree and disagree). The following weights were given 4, 3, 2and 1, respectively. Data was collected from farmers during December 2023 and January 2024, and the data was analyzed using the statistical program (SPSS). The results revealed that the reasons for farmers’ reluctance to continue using the protected agriculture for vegetables were of high importance, as the areas of reasons received weighted averages of 2.785-3.50, and this score exceeds the hypothesized mean of 2.5 degrees, With a percentage weight of 69.62 - 87.5%. The results of the study also showed that there was high approval by farmers for all the proposed treatments to ensure their using of protected cultivation to grow vegetables in Baghdad province / Al-Karkh. It can be concluded the importance of adopting the results of as a working basis for the purpose of farmers continuing to use protected cultivation for vegetables.